2021
DOI: 10.1111/dom.14308
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of dapagliflozin in treating high‐risk patients with type 2 diabetes mellitus: An economic evaluation using data from the DECLARE‐TIMI 58 trial

Abstract: Aim To undertake a cost‐effectiveness analysis of dapagliflozin in treating high‐risk patients with type 2 diabetes mellitus (T2DM), using both directly observed events in the DECLARE‐TIMI 58 trial and surrogate risk factors to predict endpoints not captured within the trial. Methods An established T2DM model was adapted to integrate survival curves derived from the DECLARE‐TIMI 58 trial, and extrapolated over a lifetime for all‐cause mortality, hospitalization for heart failure, stroke, myocardial infarction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…Our findings are similar to those published in an economic evaluation of dapagliflozin performed in the UK, in which the Cardiff T2DM model was also adapted according to the survival results of the DECLARE-TIMI 58 trial [ 45 ]. In that study, dapagliflozin was a dominant alternative compared with placebo, resulting in 0.06 more QALYs and cost-savings of £ 2,552.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings are similar to those published in an economic evaluation of dapagliflozin performed in the UK, in which the Cardiff T2DM model was also adapted according to the survival results of the DECLARE-TIMI 58 trial [ 45 ]. In that study, dapagliflozin was a dominant alternative compared with placebo, resulting in 0.06 more QALYs and cost-savings of £ 2,552.…”
Section: Discussionsupporting
confidence: 88%
“…In that study, dapagliflozin was a dominant alternative compared with placebo, resulting in 0.06 more QALYs and cost-savings of £ 2,552. These results were maintained in the subgroup analysis, which evaluated patients with established cardiovascular disease, multiple risk factors, and prior HF, and highlighted the potential of dapagliflozin to reduce the economic burden of T2DM and its associated complications [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, this would be undertaken within the context of a specific indication, eg, as a treatment for T2DM, HF, or CKD, using a CEA framework. Indeed, SGLT2is have been found to be cost-effective for the management of T2DM, 5,6 as well as for the management of patients with HF, with and without T2DM, 7 and in those with CKD, with and without T2DM. 8 However, as T2DM, CKD, and HF are closely linked in terms of pathophysiology and are integrally associated with one another within the context of health care system activity, CEA of the individual diseases may miss concomitant benefits on related diseases.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In a study based out of the United Kingdom by McEwan et al, the treatment with dapagliflozin was noted to reduce the lifetime cost by £2552 in patients with type II DM for major adverse CV events. 30 Similar favorable cost-benefit ratios were seen in studies based on Australian and Thai healthcare systems. 31 , 32 In a study performed on data extrapolated to the American healthcare system, it was found that the addition of dapagliflozin to GDMT was beneficial in terms of long term cost-benefit ratios, possibly in both diabetic and non-diabetic populations.…”
Section: Existing Literature On Role Of Dapagliflozin In Cardiorenal Diseasementioning
confidence: 55%